Opportunities and Prospects for Hydrogen Production in Azerbaijan: Steps towards the Transition to a Hydrogen Economy - Hamidova, Lala; Samedova, Elnara (International Journal of Energy Economics and Policy, 2024)
Hydrogen plays a key role in reducing greenhouse gas emissions, enabling decarbonization of the energy, transport and industrial sectors. Its importance in the energy balance will increase for several reasons. Firstly, in the modern world there is a transition to carbon-free energy, which stimulates the use of hydrogen. Secondly, a balanced system based on renewable energy sources is important to ensure stability and reliability of energy supply. The purpose of the study is to study the prospects for hydrogen production for the transition to sustainable development of the Azerbaijani economy. During the study, research methods such as graphical analysis, comparison of blue and green hydrogen production scenarios, analysis and synthesis method, and dynamic comparison method were used. The results of the study showed that in order to transition to a hydrogen economy in Azerbaijan, it is preferable to start with the production of blue hydrogen. There is potential for this in the form of rich natural gas reserves (confirmed gas reserves are 2.6 trillion cubic meters). With the advent of new technologies and lower production costs, a transition to green hydrogen will be possible. For this purpose, the country has a technical potential for renewable energy sources amounting to 135 GW on land and 157 GW at sea. The conclusions are that in order to transition to a hydrogen economy in Azerbaijan, it is necessary to adopt a strategy for transitioning the economy to a hydrogen basis, developing infrastructure, attracting investments in the modernization of chemical enterprises, and switching public transport to the use of hydrogen.